2014
DOI: 10.1071/wf13080
|View full text |Cite
|
Sign up to set email alerts
|

Numerical prediction of size, mass, temperature and trajectory of cylindrical wind-driven firebrands

Abstract: Mathematical models and numerical solution procedures for predicting the trajectory, oscillation, possible rotation, and mass and size time-evolution of cylindrical wind-driven firebrands are described and discussed. Two test problems and the results, used for validating the mathematical models, are presented. In one, experimental measurements of non-burning cylindrical particles falling in still air are compared to numerical predictions and in the other, predictions of time-evolution of mass and size of stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The firebrand equations are expressed and solved in the Lagrangian framework. Firebrands are assumed to be cylinders with a large ratio of length to diameter, undergoing both translational and rotational motions (Yin et al, 2003;Oliveira et al, 2014;Anand et al, 2018) and thermal degradation as a result of pyrolysis and charring (Morvan and Dupuy, 2004;Anand, 2018).…”
Section: Firebrand Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The firebrand equations are expressed and solved in the Lagrangian framework. Firebrands are assumed to be cylinders with a large ratio of length to diameter, undergoing both translational and rotational motions (Yin et al, 2003;Oliveira et al, 2014;Anand et al, 2018) and thermal degradation as a result of pyrolysis and charring (Morvan and Dupuy, 2004;Anand, 2018).…”
Section: Firebrand Equationsmentioning
confidence: 99%
“…They observed that for higher wind speeds, the change in the initial vertical velocity of the convective column did not affect the mean or standard deviation of the heights where the firebrands lofted or the distances they traveled to land. Yin et al (2003), Oliveira et al (2014) developed numerical models for the firebrand transport accounting for the drag, lift and gravitational forces and their effect on the rotation of firebrands to model both translational and rotational motions of cylindrical firebrands. To validate their model, Oliveira et al (2014) performed computations and experiments for a cylindrical firebrand (balsa wood) falling from an elevated point under a no ambient flow condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation of its validity for long range ember transport is beyond the scope of this paper, however we note that it is supported to some extent by the studies of Ellis (2010) and Tarifa et al (1967); in drop tests, embers either assumed an orientation of maximum drag, or tumbled but fell at a speed as if they had assumed such an orientation. Some numerical studies, including those of Koo et al (2012) and Oliveira et al (2014), include the rotational terms in the equations of motion.…”
Section: Ember Release and Transportmentioning
confidence: 99%
“…Physics based on coupled fire-atmosphere models consider approximations of the governing equations from the fluid dynamics, the combustion, and the thermal degradation of solid fuel (see, e.g., [64][65][66]) aiming to preclude the use of existing simplified empirical wildfire models because they do not predict general fire behaviour; however the high-resolution and the high-fidelity combustion are not currently appropriate because of their computational cost. Several physics based on coupled fire-atmosphere studies have been conducted (see [67][68][69][70][71][72]) and some of these studies have been applied to the fire spotting problem. Among them [71] has considered particle combustion of cylindrical and disk-shaped firebrands for several geometrical parameters.…”
Section: Introductionmentioning
confidence: 99%